From Jumbo to Dumbo: Cranial Shape Changes in Elephants and Hippos During Phyletic Dwarfing - van der Geer, Alexandra A. E.; Lyras, George A.; Mitteroecker, Philipp; MacPhee, Ross D. E. (Evolutionary biology, 2018)
Members of the mammalian families Elephantidae and Hippopotamidae (extant and extinct elephants and hippos) include extinct dwarf species that display up to 98% decrease in body size compared to probable ancestral sources. In addition to differences in body mass, skulls of these species consistently display distinctive morphological changes, including major reduction of pneumatised areas in dwarf elephants and shortened muzzles in dwarf hippos. Here we build on previous studies of island dwarf species by conducting a geometric morphometric analysis of skull morphology and allometry in target taxa, living and extinct, and elaborate on the relation between skull size and body size. Our analysis indicates that skull size and body size within terrestrial placental mammals scale almost isometrically (PGLS major axis slope 0.906). Furthermore, skull shape in dwarf species differed from both their ancestors and the juveniles of extant species. In insular dwarf hippos, the skull was subject to considerable anatomical reorganisation in response to distinct selection pressures affecting early ontogeny (the “island syndrome”). By contrast, skull shape in adult insular dwarf elephants can be explained well by allometric effects; selection on size may thus have been the main driver of skull shape in dwarf elephants. We suggest that a tightly constrained growth trajectory, without major anatomical reorganization of the skull, allowed for flexible adaptations to changing environments and was one of the factors underlying the evolutionary success of insular dwarf elephants.